Human U87 glioblastoma cells with stemness features display enhanced sensitivity to natural killer cell cytotoxicity through altered expression of NKG2D ligand. Issue 1 (December 2017) - Oh, Se-Jeong; Yang, Jung-In; Kim, Ok; Ahn, Eun-Jung; Kang, Woo; Lee, Jae-Hyuk; Moon, Kyung-Sub; Lee, Kyung-Hwa; Cho, Duck
Abstract Background Glioblastoma (GBM) is one of the most lethal tumors with a poor prognosis. Its inevitable recurrence is frequently explained by the presence of cancer stem cells. We aimed to show that human GBM cells with stemness features are more sensitive to natural killer (NK) cells than GBM cells without stemness characteristics. Methods Natural killer cell cytotoxicity was measured using flow cytometry in neurosphere-forming U87 GBM cells cultured with neurobasal media (NBE condition) and compared with that in serum-cultured U87 GBM cells (serum condition). Cytotoxicity was examined after addition of blocking NKG2D monoclonal antibodies. The expression profile of NK ligands of NK cells were investigated by reverse transcription polymerase chain reaction and western blot analysis in the U87 GBM cells in both conditions. Results NBE U87 cells showed higher cytotoxicity to NK cells than serum U87 cells did (55 vs 35% at an effector to target cell ratio of 5:1). The increased cytotoxicity was diminished in NBE U87 cells by a larger gap than in serum U87 cells by adding NKG2D blocking antibodies. Of the NKG2D ligands, the expression of ULBP1 and ULBP3 was relatively increased in NBE U87 cells compared to serum U87 cells. Conclusions U87 GBM cells with stemness features demonstrate increased cytotoxicity to NK cells in association with altered NKG2D ligand expression of NK cell activating receptor. Applying immune modulation to GBM treatment may be a promising adjuvant therapy in patients with intractable GBM.